Inequality in relational wealth within the upper societal segment: evidence from prehistoric Central Europe - Johannes Marzian; Julian Laabs; Johannes Müller; Tilman Requate (Humanities and Social Sciences Communications, 2024)
While our understanding of long-term trends in material wealth inequality in prehistoric societies has expanded in recent decades, we know little about long-term trends in other dimensions of wealth and about social developments within particular societal segments. This paper provides the first evidence of inequality in relational wealth within the upper societal segment of a supra-regional network of communities in prehistoric Central Europe over the first four millennia BCE. To this end, we compiled a novel dataset of 5000 single-funeral burial mounds and employed burial mound volume as a proxy for the buried individual's relational wealth. Our analysis reveals a consistently high level of inequality among the buried individuals, showing a wave-like pattern with an increasing trend over time. Additionally, our findings show temporal shifts in the size of the upper societal segment. Based on a review of archeological and paleo-environmental evidence, the temporal change in inequality may be explained by technological progress, climate and population dynamics, trade and social networks, and/or sociopolitical transformations.
Keywords: N33; 330; Economic History; Social Inequality; Burial Mound Data; Waves of Inequality; Prehistorical Central Europe